2020
DOI: 10.1038/s41598-020-77552-7
|View full text |Cite
|
Sign up to set email alerts
|

Radiomic prediction of radiation pneumonitis on pretreatment planning computed tomography images prior to lung cancer stereotactic body radiation therapy

Abstract: This study developed a radiomics-based predictive model for radiation-induced pneumonitis (RP) after lung cancer stereotactic body radiation therapy (SBRT) on pretreatment planning computed tomography (CT) images. For the RP prediction models, 275 non-small-cell lung cancer patients consisted of 245 training (22 with grade ≥ 2 RP) and 30 test cases (8 with grade ≥ 2 RP) were selected. A total of 486 radiomic features were calculated to quantify the RP texture patterns reflecting radiation-induced tissue reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 32 publications
5
33
1
Order By: Relevance
“…We believe that our data reflect the population of esophageal cancer patients since patient characteristic (age, sex and tumor stage) were similar to other study of esophageal cancer [ 27 , 29 , 37 ]. The incident of RP grade ≥ 2 in esophageal cancer was report by systematic review about 6.6% which similar to our study (5%), although information for grade 1 RP were lacking.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We believe that our data reflect the population of esophageal cancer patients since patient characteristic (age, sex and tumor stage) were similar to other study of esophageal cancer [ 27 , 29 , 37 ]. The incident of RP grade ≥ 2 in esophageal cancer was report by systematic review about 6.6% which similar to our study (5%), although information for grade 1 RP were lacking.…”
Section: Discussionsupporting
confidence: 88%
“…The minority class in the training set was randomly oversampled with replacement to equalize the two classes. Multivariate logistic regression with L1 norm regularization (LASSO) was used [ 25 27 ]. LASSO was performed to prevent overfitting and can also be used as embedded feature selection in the logistic regression model by shrinking the coefficient of unimportant features to zero.…”
Section: Methodsmentioning
confidence: 99%
“…Through quantitative assessment of FDG PET/CT imaging before and after radiation therapy in stage III NSCLC patients, a pilot study suggested that global lung parenchymal glycolysis and lung parenchymal SUVmean may serve as potentially useful biomarkers to lung inflammation after thoracic radiation therapy [ 154 ]. Moreover, based on pretreatment planning CT in patients after SBRT delivery, the radiomic predictive model of lung volume irradiated with more than 5 Gy (LV5) was considered the best for RP estimation than the DVH model [ 155 ]. By the combination use of cone-beam CT radiomics features (NGTDM25: Contras and others) and two pretreatment CT radiomics features (SHAPE: Mass and SHAPE: Orientation), the prediction specificity of lung toxicity was further improved from 80.77% to 84.62% after SBRT in stage I NSCLC patients [ 156 ].…”
Section: Potential Biomarkers For Monitoring Radiation-induced Lung Injurymentioning
confidence: 99%
“…The potential of planning computed tomography (pCT) image signatures in the prediction of RP status after SABR has been explored in previous radiomics studies [ 12 , 13 ]. Hirose et al utilized histogram and texture features extracted from pCT and wavelet decomposition (WD) images, which have been widely used in radiomics studies, to construct the image signature and prediction model using the least absolute shrinkage and selection operator logistic regression (LASSO-LR) [ 13 ]. Moran et al attempted to develop a LR model for the classification of the RP status based on the image features extracted from the pCT as well as the post-SABR diagnostic CT images [ 12 ].…”
Section: Introductionmentioning
confidence: 99%